A Review Of Studies Related To Arabic Language Learning Based On The Common European Framework Of Reference For Language (CEFR) - Mohammad Roshimi Abdullah; Mohd Aizul Yaakob; Muhammad Firdhaus Zulkifli; Muhammad Sabri Sahrir (Ijaz Arabi Journal of Arabic Learning, 2023)
In 2001, the European Union (CoE) introduced the Common European Framework of Reference for Language (CEFR) to measure the competency and mastery of languages found in Europe and other languages in the world. In the context of Arabic language education, Saudi Arabia was one of the first countries to implement Arabic language proficiency measurements based on CEFR standards, particularly at Umm al-Qura University, Mecca, and Saudi Electronic University. This article aims to gather studies related to Arabic language proficiency based on the CEFR standard. In addition, this article also provides added value by analyzing each study to provide an explicit overview of the studies. To achieve the goal, qualitative methods are used, where library methods and document analysis are practiced. CEFR-related studies and articles will be collected and analyzed using inductive and deductive methods. The analysis of these findings has also found that five main themes have been debated. Among them is the need to establish a proficiency standard in Arabic. There is consensus among some Arabic language experts that the proficiency standard for the Arabic language needs to be established along with other world languages. Apart from that, some experts also think that it is necessary to have indicators of Arabic language proficiency based on CEFR standards. This is considering that this standard has been used in the measurement of proficiency for some other languages of the world.